The Historical Evolution and Cultural Symbolism of the United Kingdom - Jo’raxo’jayeva, Malohatxon (Journal of Innovation in Education and Social Research, 2026)
This article presents a comprehensive study of the United Kingdom's rich historical heritage and its cultural identity as reflected through national symbols. The research examines key stages of British history—from the Roman conquest and the formation of the medieval monarchy to the peak of the British Empire. A significant portion of the paper is dedicated to the origins and social significance of symbols such as the Union Jack, the national anthem, the figure of Britannia, and various national floral emblems. Each symbol is analyzed not merely as a visual mark but as a complex product of centuries-old political unions and cultural values. The study evaluates the impact of historical events on the evolution of symbolism and assesses their contemporary relevance in British society. Furthermore, the research explores the preservation of national identity and the role of traditional symbols within the context of modern globalization.